Marriage Mahar to Minimize the Low Rate of Marriage in Aceh Pidie, Indonesia - Sitompul, Roswita; Alesyanti, Alesyanti; Hakim, Nurul (Italian Sociological Review, 2018)
The value of mahar in Aceh Pidie occupies the number two expensive in Indonesia after Sulawesi, one of Indonesia Province. Mahar in Aceh Pidie is attributed to gold measured in mayam. Mayam itself is referring to a kind of gold dosage prevailing in the people of Aceh. If converted with grams, one Mayam is estimated to be worth about 3.33 grams. Now, the price of one mayam is close to one million eight hundred thousand rupiah. Please imagine a marriage mahar provisions in Aceh Pidie sets to 50-70 mayam. What a expensive price that should be paid by the prospective bridegroom to engaged a woman. A man should provide funds of 90 to 126 million, and it does not include premium amenities and asoe talam (a set of suit). This is a very urgent problem on customary rules, which can not be regarded as a fairness. This issue needs to be handled very carefully. We can examine and give contribution to handling it. Departing from the fact, this study aims to find an alternative to the concept and application of the marriage mahar in Aceh Pidie. Mahar who arbitrates ‘shall’, which makes the people of Aceh Pidie choose not to obey much and they choose to the road elope or kawin lari, locked horns with traditional leaders that impact disharmony cultural order within existing communities. The most severe course can also occur, such as sex outside of marriage because the delay time of the wedding, as a consequence of unmet mahar.